EVALUATING THE EFFECTIVENESS OF USING EDUCATIONAL RESOURCES IN EDUCATION WITH THE HELP OF SOCIAL NETWORKS (The Role of Exact Sciences in the Era of Modern Development, 2023)
In this article, the selections that can be used to create a number of educational resources for young people through social networks are announced to the public through social networks, and to study the demand for the necessary resources for young people.